A Nonlinear Directional Derivative Scheme for Edge Detection - Muammer Catak (Institute of Advanced Engineering and Science, 2012)
In this paper, a new one-stage nonlinear directional derivative scheme has been proposed for edge detection. The directional edge detection method was applied to gray and color images. The results were compared to three well-known conventional edge detectors namely Canny, Prewitt, and Sobel. The directional derivative method is an efficient edge detection tool especially in capturing details.DOI:http://dx.doi.org/10.11591/ijece.v2i4.750